2003
DOI: 10.1002/nme.755
|View full text |Cite
|
Sign up to set email alerts
|

Discrete equivalent time integration methods for transient analysis

Abstract: SUMMARYIt was recently shown in a series of papers that the frequency response of temporally discretized ÿnite element equations and, consequently, the achievable accuracy cannot be manipulated independently in di erent frequency ranges. In addition, there exist limitations on the achievable accuracy of a time integration method no matter what the order of accuracy of the method is. Motivated by this fact, a family of time integration methods is derived in the time domain based on the principle that the exact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Figures 4 and 5 depict the algorithmic damping ratio and relative period error for several different time integration algorithms (Hulbert, 1992a). An interesting controls perspective on numerical dispersion and dissipation can be found in Muǧan and Hulbert (2001a,b) and Muǧan (2003). In a similar vein, Pegon (2001) characterizes algorithm performance in terms of forced vibration response.…”
Section: Dispersion and Dissipationmentioning
confidence: 98%
“…Figures 4 and 5 depict the algorithmic damping ratio and relative period error for several different time integration algorithms (Hulbert, 1992a). An interesting controls perspective on numerical dispersion and dissipation can be found in Muǧan and Hulbert (2001a,b) and Muǧan (2003). In a similar vein, Pegon (2001) characterizes algorithm performance in terms of forced vibration response.…”
Section: Dispersion and Dissipationmentioning
confidence: 98%
“…Many approaches have been established to solve different dynamic problems, such as structure, fluid flowing, and multi-rigid-body systems [3][4][5][6][7][8][9][10][11][12]. They are mainly classified into two categories: explicit and implicit algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…List of some of the available criteria for investigating the performance of integration algorithms are listed in [3]. One of the studies on the performance evaluation of integration algorithms was carried out by Mugan in which he found that frequency domain analysis can describe all of the time domain properties of an integration algorithm [4]. A frequency domain analysis will also be used in this paper to evaluate different integration algorithms.…”
Section: Introductionmentioning
confidence: 99%